2011
DOI: 10.1002/ejoc.201100066
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoximine‐Directed Single and Double ortho‐Lithiation: Stereoselective Rearrangements of o,o′‐Dilithiophenylsulfoximines to o,N‐Dilithiosulfinylanilines through Anionic Fries Rearrangements of o,o′‐Dilithiophenylsulfinamides

Abstract: Treatment of various phenylsulfoximines with nBuLi (1 equiv.) at -78°C in THF resulted in single ortho-lithiations and gave the corresponding o-lithiosulfoximines. According to NMR spectroscopy, the o-lithiosulfoximines are generally stable at 0°C. The o-lithiosulfoximines were efficiently trapped through deuteration, alkylation, silylation, and phosphanylation. Treatment of cyclic phenylsulfoximines also containing H atoms at their α-positions with nBuLi (1 equiv.) at -78°C furnished the o-lithiosulfoximines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…The sulfoximine unit in 4 is an excellent ortho-director of lithiation. 4,6 This is seen on addition of butyl lithium to sulfoximine 4 which apparently leads to formation of the o-lithio derivative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfoximine unit in 4 is an excellent ortho-director of lithiation. 4,6 This is seen on addition of butyl lithium to sulfoximine 4 which apparently leads to formation of the o-lithio derivative.…”
Section: Resultsmentioning
confidence: 99%
“…But having o-silyl compound 5 in hand, an iododesilylation 7 approach to 6 seemed to offer an attractive alternative (Scheme 2). However, when 5 is treated with iodine chloride, the product is not the expected iodide 6, but a totally different type of product which was identified as the 3H-1λ 6 : S1-O10 1.451, S1-N2 1.512, S1-C9 1.792, S1-C11 1.828, Si3-N2 1.721, Si3-C8 1.886.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, α‐branched sulfones lacking the additional γ‐branching deprotonated as usual in the α‐position, leading directly to III . The Gais group found a similar DoM/transmetalation behavior for conformationally constrained sulfoximines 5…”
Section: Introductionmentioning
confidence: 85%
“…On the other hand, two consecutive proton transfers may first lead to an ortho ,α‐dilithium intermediate VIII and substrate IV as the rate‐limiting step, from which a second, potentially fast proton transfer follows, leading to two units of IX . Indeed, intermediates VIII were previously individually generated by Gais and colleagues by a reverse strategy of initial α‐ and subsequent ortho ‐metalation 5,7…”
Section: Introductionmentioning
confidence: 99%
“…(1) n-BuLi, −78°C More recently, Gais and coworkers [153] have used cyclic alkylsulfoximines for evaluating the selectivity of ortho-versus α-metalation. They found that lithiation in ortho-position was favored at low temperature (−50 • C), whereas the proportion of the α-metalated product becomes larger (even quantitative) by increasing the temperature.…”
Section: Sulfoximinesmentioning
confidence: 99%